THE PRIORITY NEEDS OF PRIVATE PRIMARY SCHOOL MANAGEMENT BASED ON THE CONCEPT OF STUDENT INNOVATIVE LEADERSHIP - Boonkua, Hassatorn; Chaemchoy, Sukanya; Siribanpitak, Pruet (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2020)
The purpose of this research was to study the priority needs of private primary school management based on the concept of student’s innovative leadership, focusing on the management of the academics and students’ affairs. While the research is centered around curriculum management, learning management, and assessment and evaluation on the academic’s side, it examines the students’ affairs management in aspects of performance-enhancing activities and extracurricular activities. The sample group used in this research consists of 340 private primary schools in Thailand, selected through the multi-stage random sampling method. The informants are 560 informants school directors and teachers. The instrument used in this study was a 5-level rating-scale questionnaire. The data was analyzed by using frequency distribution, percentage, mean, standard deviation, and the Modified Priority Needs Index (PNI modified). The findings indicate that, for the academic management, assessment and evaluation of students’ performance receives the highest priority needs index, followed by curriculum management and learning management. On the other hand, the highest priority needs index is given to performance-enhancing activities and extracurricular activities, respectively for the student affairs management. Overall it is found that promoting primary students’ creativity and ability to innovate have high priority needs in all aspects of private primary school management.